2020
DOI: 10.1007/s00428-020-02934-1
|View full text |Cite
|
Sign up to set email alerts
|

Fibrotic progression and radiologic correlation in matched lung samples from COVID-19 post-mortems

Abstract: Data on the pathology of COVID-19 are scarce; available studies show diffuse alveolar damage; however, there is scarce information on the chronologic evolution of COVID-19 lung lesions. The primary aim of the study is to describe the chronology of lung pathologic changes in COVID-19 by using a post-mortem transbronchial lung cryobiopsy approach. Our secondary aim is to correlate the histologic findings with computed tomography patterns. SARS-CoV-2-positive patients, who died while intubated and mechanically ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
77
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 37 publications
6
77
0
3
Order By: Relevance
“…In addition, autoptic results revealed that in about 48% of cases the predominant histopathological finding were capillary congestion, microthrombi as well as moderate intra-alveolar fibrin exudation resultant in exudative disseminate alveolar damage and superimposed bronchopneumonia ( 135 ). A more widespread histological pattern of alveolar damage with greater fibrotic evolution in the lungs was observed in patients who died after a long period of mechanical ventilation ( 136 ). In few cases, an intra-alveolar deposition of neutrophilic granulocytes, probably due to superimposed bacterial infection, was also detected ( 137 ).…”
Section: Sars-cov-2 Clinical Implication and Potential Mutual Interacmentioning
confidence: 99%
“…In addition, autoptic results revealed that in about 48% of cases the predominant histopathological finding were capillary congestion, microthrombi as well as moderate intra-alveolar fibrin exudation resultant in exudative disseminate alveolar damage and superimposed bronchopneumonia ( 135 ). A more widespread histological pattern of alveolar damage with greater fibrotic evolution in the lungs was observed in patients who died after a long period of mechanical ventilation ( 136 ). In few cases, an intra-alveolar deposition of neutrophilic granulocytes, probably due to superimposed bacterial infection, was also detected ( 137 ).…”
Section: Sars-cov-2 Clinical Implication and Potential Mutual Interacmentioning
confidence: 99%
“…Barisione, et al performed a study on transbronchial biopsy autopsy specimens in patients who succumbed to COVID-19. Their data demonstrated phases of alveolar damage secondary to SARS-CoV-2, with the final phase culminating in interstitial fibroblast proliferation with sparse collagen fiber deposition ( 19 ). These data are in concert with recent radiology data demonstrating the development of pulmonary fibrosis on chest CT. Fang, et al presented a case series of 12 patients in the recovery period of severe COVID-19 infection in which there was gradually development of increasing fibrosis ( 20 ).…”
Section: Cardiothoracic Systemmentioning
confidence: 99%
“…he novel SARS-CoV-2 virus is responsible for the Coronavirus-19 (COVID- 19) illness, which has affected millions worldwide and continues to spread. The virus was first identified in connection with an outbreak of pneumonia in Wuhan City, Hubei province, China in December 2019 (1,2).…”
mentioning
confidence: 99%
“…Pulmonary coagulopathy is once again receiving attention because pulmonary thrombosis is frequently seen in patients with COVID-19 pneumonia, 7 , 8 causing increased dead space and severe hypoxaemia. The promising findings of the CHARLI study 3 underline the importance of considering studies of nebulised heparin in patients with COVID-19 pneumonia, 9 and some studies have already been registered on ClinicalTrials.gov ( NCT04397510 , NCT04530578 ).…”
mentioning
confidence: 99%